2021
DOI: 10.1111/jfpe.13751
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of functional, textural, and thermal properties of soluble complex of whey protein–xanthan gum hydrogel

Abstract: Extensive employment of hydrogels in various industry especially food areas of applications is considered to be of prime importance. The current research is focused on producing a heat-induced hydrogel consisting of whey protein concentrate (WPC) and different concentrations of xanthan gum (XG) (0, 0.01, 0.3, and 0.6%) to develop the texture and thermal stability of WPC hydrogel. The soluble complex of WPC-XG, which was created in pH 6, was used to fabricate hydrogels. The Fourier transform infrared, scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The presence of this peak indicated that MCZ was crystalline [ 36 ]. A melting endothermic peak is seen in XGM at 151 °C, while a degrading exothermic peak is seen at 277 °C [ 37 ]. TXGM showed an endothermic peak at 99 °C, this decrease in melting temperature was due to the easily breakable thiol groups.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of this peak indicated that MCZ was crystalline [ 36 ]. A melting endothermic peak is seen in XGM at 151 °C, while a degrading exothermic peak is seen at 277 °C [ 37 ]. TXGM showed an endothermic peak at 99 °C, this decrease in melting temperature was due to the easily breakable thiol groups.…”
Section: Resultsmentioning
confidence: 99%
“…The dried and unground hydrogel samples were sprayed with gold, and the surface morphology of the samples was observed by SEM at 10 kV accelerating voltage [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, several gums have shown great complex binding with milk protein. In this context, Pilevaran et al [ 77 ] synthesized the hydrogel using whey protein and xanthan gum. In their study, different amounts of gums were used for the synthesis of the hydrogel.…”
Section: Characterization Of Milk Protein Hydrogelsmentioning
confidence: 99%